The SCUBA-2 Large eXtragalactic Survey: 850μm map, catalogue and the bright-end number counts of the XMM-LSS field. Issue 3 (30th January 2023) - Garratt, T K; Geach, J E; Tamura, Y; Coppin, K E K; Franco, M; Ao, Y; Chen, C -C; Cheng, C; Clements, D L; Dai, Y S; Dannerbauer, H; Greve, T R; et al.
ABSTRACT: We present 850 μ m imaging of the XMM -LSS field observed for 170 h as part of the James Clerk Maxwell Telescope SCUBA-2 Large eXtragalactic Survey (S2LXS). S2LXS XMM -LSS maps an area of 9 deg^2, reaching a moderate depth of 1σ 4 mJy beam^-1 . This is the largest contiguous area of extragalactic sky mapped by James Clerk Maxwell Telescope (JCMT) at 850 μ m to date. The wide area of the S2LXS XMM -LSS survey allows us to probe the ultra-bright (S_850μ m15 mJy ), yet rare submillimetre population. We present the S2LXS XMM -LSS catalogue, which comprises 40 sources detected at >5σ significance, with deboosted flux densities in the range of 7 –48 mJy . We robustly measure the bright-end of the 850 μ m number counts at flux densities 7 mJy, reducing the Poisson errors compared to existing measurements. The S2LXS XMM -LSS observed number counts show the characteristic upturn at bright fluxes, expected to be motivated by local sources of submillimetre emission and high-redshift strongly lensed galaxies. We find that the observed 850 μ m number counts are best reproduced by model predictions that include either strong lensing or source blending from a 15-arcsec beam, indicating that both may make an important contribution to the observed overabundance of bright single dish 850 μ m selected sources. We make the S2LXS XMM -LSS 850 μ m map and >5σ catalogue presented here publicly available.